2019
DOI: 10.1002/pon.5125
|View full text |Cite
|
Sign up to set email alerts
|

The importance of staying connected: Mediating and moderating effects of social group memberships on psychological well‐being after brain tumor

Abstract: Objective Functional impairments can lower psychological well‐being after brain tumor. Changes in social groups and confidence in support potentially impact this relationship. This study aimed to investigate the influence of social group memberships (SGMs) on the relationship between perceived cognitive and physical impairment and psychological well‐being. Methods Seventy adults (60% female) with primary brain tumor (46% benign; 18% low grade; 36% high grade) aged 22 to 75 years undertook a brief cognitive tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Thus, exercise and training are essential to achieving a beneficial outcome (Baima et al, 2017;Capozzi et al, 2016;Hansen et al, 2018;Shahpar et al, 2018), just as exercise may increase not only functional independence but also play a role in well-being (Baima et al, 2017). Moreover, functional impairment may result in a greater risk of experiencing a loss of social group membership (Cubis et al, 2019) as patients become limited in their ability to interact socially. The feeling of solidarity between patients and family caregivers is valuable, and caregivers often possess a significant capacity to be engaged in the care and support of the patient with HGG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, exercise and training are essential to achieving a beneficial outcome (Baima et al, 2017;Capozzi et al, 2016;Hansen et al, 2018;Shahpar et al, 2018), just as exercise may increase not only functional independence but also play a role in well-being (Baima et al, 2017). Moreover, functional impairment may result in a greater risk of experiencing a loss of social group membership (Cubis et al, 2019) as patients become limited in their ability to interact socially. The feeling of solidarity between patients and family caregivers is valuable, and caregivers often possess a significant capacity to be engaged in the care and support of the patient with HGG.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there was continual, negatively affected family functioning during the brain cancer trajectory as perceived by both patients and caregivers. Hence, family-focused interventions focusing on how to maintain social participation and supportive relationships are warranted (Cubis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the most consistent predictor of QoL was the number of social contacts when assessed weekly over a period of 12 weeks in brain tumor patients during the first lockdown of the COVID pandemic [125]. This study highlighted the impact of social group membership on wellbeing in brain tumor patients which probably is also valid independently of the COVID pandemic [90]. Additionally, some studies demonstrated a positive influence of psychotherapeutic interventions targeting psychosocial issues [114] and indicated the positive influence of supportive social relationships on the well-being of brain tumor patients in general [90].…”
Section: Psychosocial Burdenmentioning
confidence: 66%
“…The main areas referred to as the social brain encompass the medial prefrontal cortex, superior temporal sulcus, temporal-parietal junction, amygdala and insula [12]. Social relationships contribute to resilience [13]-i.e., the ability to maintain high levels of functioning in the context of adversity-and are known to buffer the adverse effects of illness on psychological well-being [14]. Social cognition is an umbrella term for mental processes associated with interpersonal interactions [15], facilitating adequate social behavior and fostering social relationships, consequently contributing to QoL [16].…”
mentioning
confidence: 99%